Makna dan Strategi Kewirausahaan Usaha Kuliner Pagi Hari dalam Meningkatkan Perekonomian Keluarga dan Keberlanjutan Usaha - Ery Suryanti; Hendra Lesmana; Bernadette Cahya Putri Utami (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2026)
This research is a qualitative descriptive study, namely research that produces descriptive data in oral or written form. By using a qualitative descriptive approach and the research objects are six morning business actors using a purposive sampling technique. The data used are primary and secondary data, data obtained from observations, data obtained also comes from direct surveys at sales locations and various information obtained to complement the research data. The purpose of this study is to analyze the meaning and strategy of morning culinary entrepreneurship in improving family economics and business sustainability. Data analysis techniques from data presentation to data collection. The results of the study indicate that morning culinary businesses have an important role in the family economy. Morning culinary entrepreneurs earn income from sales to meet daily needs. Business sustainability is supported by the skills of processing ingredients into products and motivational encouragement from the family. This study also provides an overview that morning culinary businesses have the potential to empower the family economy by improving skills, product innovation and support.